English Language Learners in the State of Maine: Early Education Policy That Can Make a Difference - Oldham, Erin; Atkins, Julie; Ward, Helen (Maine Policy Review, 2009)
The authors discuss the increasing number of Maine children who are English language learners (ELL) or who are limited-English proficient (LEP), noting that insufficient attention has been paid to the preschool education of this group. The authors describe lessons learned from an Early Reading First Program in Portland, which enhanced the school-readiness of preschool ELL children.